Potential determinants of the E/e′ ratio in non‐dialysis compared with dialysis patients. Issue 12 (27th July 2021) - Hsu, Hon‐Chun; Norton, Gavin R.; Robinson, Chanel; Woodiwiss, Angela J.; Dessein, Patrick H.
Abstract: Aim: We hypothesized that arterial function and N‐terminal natriuretic peptide (NT‐proBNP) levels as a marker of volume overload, relate differently to E/e′ as an index of diastolic function in dialysis compared with non‐dialysis patients with chronic kidney disease. We further examined whether cardiovascular risk factors attenuated these relationships. Methods: We assessed cardiovascular risk factors and determined arterial function indices by applanation tonometry using SphygmoCor software and E/e′ by echocardiography in 103 (62 non‐dialysis and 41 dialysis) patients. Results: In established confounder adjusted analysis, dialysis status impacted the pulse wave velocity‐E/e′ relationship (interaction p  = .01) but not the NT‐proBNP level‐E/e′ association (interaction p  = .1). Upon entering arterial function measures and NT‐proBNP levels simultaneously in regression models, arterial function measures were associated with E/e′ ( p  = .008 to .04) in non‐dialysis patients whereas NT‐proBNP levels were related to E/e′ in dialysis patients ( p  = .009 to .04). Bivariate associations were found between diabetes ( p  < .0001) and E/e′ in non‐dialysis patients, and haemoglobin concentrations and E/e′ ( p  = .02) in those on dialysis. Upon adjustment for diabetes in non‐dialysis patients, only central pulse pressure remained associated with E/e′ ( p  = .02); when haemoglobin concentrations were adjusted for in dialysis patients, NT‐proBNP levels were no longer associated with E/e′ ( p  = .2). In separate models, haemoglobin levels were associated with E/e′ independent of left ventricular mass index and preload and afterload measures ( p  = .02 to .03). Conclusion: The main determinants of E/e′ may differ in non‐dialysis compared with dialysis patients. These include arterial function and diabetes in non‐dialysis patients, and volume overload and anaemia in dialysis patients. SUMMARY AT A GLANCE: Impaired diastolic function is prevalent and problematic in people with chronic kidney disease. Using the ratio of E to e′ as a measure of impaired diastolic function, the factors most strongly associated with this metric were different depending on whether participants had dialysis‐dependent CKD or not.